2010
DOI: 10.1111/j.1399-3089.2009.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of α1,3-galactosyltransferase knockout pig heart and kidney glycolipids and their reactivity with human and baboon antibodies

Abstract: GalT-KO pig heart and kidney completely lacked Gal glycolipid antigens whilst glycolipids synthesized by competing pathways were increased. Baboon and human serum antibodies showed a different reactivity pattern to pig glycolipid antigens indicating that non-human primates have limitations as a human pre-clinical model for immune rejection studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 46 publications
5
78
1
Order By: Relevance
“…The induced non-Gal antibody response may also react with carbohydrate or glycolipid epitopes. Consistent with this an induced primate response to an undefined acidic cardiac glycolipid has recently been reported (11,12). In this report, we used retrovirus-encoded expression libraries, produced from GT ϩ :CD46 and GTKO PAECs, to identify the target antigens detected by induced non-Gal antibody after pig-to-primate cardiac xenotransplantation.…”
supporting
confidence: 60%
“…The induced non-Gal antibody response may also react with carbohydrate or glycolipid epitopes. Consistent with this an induced primate response to an undefined acidic cardiac glycolipid has recently been reported (11,12). In this report, we used retrovirus-encoded expression libraries, produced from GT ϩ :CD46 and GTKO PAECs, to identify the target antigens detected by induced non-Gal antibody after pig-to-primate cardiac xenotransplantation.…”
supporting
confidence: 60%
“…Such studies were also able to show that pigs do not express the Forssman antigen (a glycolipid against which humans have several antibodies), as shown by the presence of the high levels of anti-Forssman antibodies and the absence of Forssman antigens in pig tissues. Unexpectedly, the same study found that baboons immunized with GalT-KO pig cells had no significantly increased IgM and IgG binding to aGal-tri, or any of the saccharides in the panel considered, a finding that contrasts with the report from Diswall et al (2010), who identified a different pattern of glycolipid expression in organs from GalT-KO pigs. The P 1 antigen (not seen in wildtype kidneys) was detected in the GalT-KO line, for instance.…”
Section: Antibody-mediated Xenograft Rejectionmentioning
confidence: 80%
“…It has now been shown, in fact, that another enzyme called iGb 3 synthase leads to aGal epitope production in GalT-KO animals (Sharma et al 2003), although this has not been confirmed by other investigators (Diswall et al 2010(Diswall et al , 2011Fang et al 2012;Puga Yung et al 2012;Tahiri et al 2013). In any case, the levels of both IgM and IgG anti-aGal antibodies remain stable after GalT-KO xenografts have been transplanted into nonhuman primates (Chen et al 2005;Kuwaki et al 2005), suggesting that-with the coverage afforded by current immunosuppression-any remaining aGal epitopes are poorly immunogenic and may not be responsible for any graft damage.…”
Section: Antibody-mediated Xenograft Rejectionmentioning
confidence: 92%
See 1 more Smart Citation
“…To overcome the shortage of donor organs, fundamental research of xenotransplant has become the focus of attention. [1][2][3][4] Many researchers indicate this as the study object of xenotransplant, [5][6][7] the porcine liver is a reasonable and attention-drawing donated organ. The porcine liver and anastomosis of blood vessels are extremely similar to the human's in anatomy and hemodynamics; the research of pig-to-human liver xenotransplant is increasing.…”
Section: Introductionmentioning
confidence: 99%